Development, regeneration, and physiological expansion of functional β-cells: Cellular sources and regulators - Chernysheva, М. B.; Ruchko, Е. S.; Karimova, М. V.; Vorotelyak, Е. A.; Vasiliev, А. V. (Frontiers in Cell and Developmental Biology, 2024)
Pancreatic regeneration is a complex process observed in both normal and pathological conditions. The aim of this review is to provide a comprehensive understanding of the emergence of a functionally active population of insulin-secreting β-cells in the adult pancreas. The renewal of β-cells is governed by a multifaceted interaction between cellular sources of genetic and epigenetic factors. Understanding the development and heterogeneity of β-cell populations is crucial for functional β-cell regeneration. The functional mass of pancreatic β-cells increases in situations such as pregnancy and obesity. However, the specific markers of mature β-cell populations and postnatal pancreatic progenitors capable of increasing self-reproduction in these conditions remain to be elucidated. The capacity to regenerate the β-cell population through various pathways, including the proliferation of pre-existing β-cells, β-cell neogenesis, differentiation of β-cells from a population of progenitor cells, and transdifferentiation of non-β-cells into β-cells, reveals crucial molecular mechanisms for identifying cellular sources and inducers of functional cell renewal. This provides an opportunity to identify specific cellular sources and mechanisms of regeneration, which could have clinical applications in treating various pathologies, including in vitro cell-based technologies, and deepen our understanding of regeneration in different physiological conditions.